Investigation and study of “The Part of the Benefits of Abi Al-Qasim Ali Bin Abdul-Rahman Bin Al-Hussein Bin Alik Al-Nisaburi on the Authority of His Elders (Deceased: 468 AH)” - بلح, عبد الرحمن السيد السيد عبد الغفار (Islamic Religious Education Departement, 2023)
تناولت هذه الدراسة تحقيق هذا المخطوط، وهذا المخطوط يُعد تحقيق لجزء حديثي مهم ألاوهو: